Ventral and dorsal streams in the evolution of speech and language - Rauschecker, Josef P. (Frontiers in Evolutionary Neuroscience, 2012)
The brains of humans and old-world monkeys show a great deal of anatomical similarity. The auditory cortical system, for instance, is organized into a ventral and a dorsal pathway in both species. A fundamental question with regard to the evolution of speech and language (as well as music) is whether human and monkey brains show principal differences in their organization (e.g. new pathways appearing as a result of a single mutation), or whether species differences are of a more subtle, quantitative nature. There is little doubt about a similar role of the ventral auditory pathway in both humans and monkeys in the decoding of spectrally complex sounds, which some authors have referred to as auditory object recognition. This includes the decoding of speech sounds (“speech perception”) and their ultimate linking to meaning in humans. The originally presumed role of the auditory dorsal pathway in spatial processing, by analogy to the visual dorsal pathway, has recently been conceptualized into a more general role in sensorimotor integration and control. Specifically for speech, the dorsal processing stream plays a role in speech production as well as categorization of phonemes during on-line processing of speech.